(3cGHhS GdEQgGH h SbhW GdCbfYI (B/s - (3fGaY, EHQGgjes ([(3Ohf ecGf(B] :s (3GdeDSSI GdhWfjI ddfTQ h GdETgGQ(B;(3eDSSI GdCgQGe ,s, 2002)
(3aj gPG GdcJGH jcTa GdcGJH hGbY GdhKGFb h GdJbGQjQ Yf LPhQ GdGQgGH cXGgQI JGQjNjI h GdOhQ GdNGQLj aj h OhQ GdYhGed GdeMdjI hjMOO edGeM GdTNUjI GdGQgGHjI h jfGbT NW GdOaGY GdGhd VO GdGQgGH h jLjH Yf SDGd Mhd LOhi GdMhGQ eY GdGQgGH h jYQV NWI TGedI ddJYGedeY gPg GdeTcdI aj eUQs
(3HjHd U(B..:212s
Keywords: (3JGQjNs; (3GdEQgGHs